2010
DOI: 10.4070/kcj.2010.40.6.292
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of an Iatrogenic Giant Femoral Artery Pseudoaneurysm With Percutaneous Thrombin Injection

Abstract: A femoral artery pseudoaneurysm (FAP) is one of the most troublesome complications following invasive procedures related to the femoral arterial access. Post-procedure FAP rarely occurs; however, its occurrence tends to increase with the more frequently antiplatelet agents, anticoagulants, and larger-sized catheter used for interventional procedures. Traditionally, surgical repair has been considered as the standard treatment modality for FAP; however, less invasive methods currently exist such as blind manual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Although inflating a balloon at the site of the neck of a PSA in order to prevent leakage of thrombin into the artery has been described, 12 ) an additional puncture is necessary to do this, and we generally avoid this to limit the risk of further bleeding complications. Moreover, unlike the standard method (described herein) in which injection is finished as soon as persistent flow inside the PSA disappears, using a balloon creates the risk of administering excess dose of thrombin.…”
Section: Discussionmentioning
confidence: 99%
“…Although inflating a balloon at the site of the neck of a PSA in order to prevent leakage of thrombin into the artery has been described, 12 ) an additional puncture is necessary to do this, and we generally avoid this to limit the risk of further bleeding complications. Moreover, unlike the standard method (described herein) in which injection is finished as soon as persistent flow inside the PSA disappears, using a balloon creates the risk of administering excess dose of thrombin.…”
Section: Discussionmentioning
confidence: 99%
“…And the diameter of postcatheterization pseudoaneurysm average size was 4.4 cm in this case series [9]. We found that there were 2 cases that which are termed as giant and the diameters were 55x30 mm and 45x30x50 mm, respectively in literature [10,11].…”
Section: Discussionmentioning
confidence: 99%